Proven Strategies for Achieving Superior Work Performance - Odum, Bili A. (Nigeria, 2008)
How to Excel at Work is a store of extensively researched, time-tested and proven strategies and techniques that you can gain mastery of and apply in any workplace to put yourself on the path of career distinction...
Keywords: Industrial Psychology; Non-Fiction; Work Accomplishment